Synergistic effect of metformin and fenugreek on the lipid profile of type-II diabetic patients - Kaur, Manmeet; Singh, Narinder (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Fenugreek is a traditional herb which has great relevance in the world since time immemorial due to its multifarious uses. Besides being a rich source of nutrition, it also finds place in the cure of certain pathological conditions. One of its highly beneficial effects is have been observed on the lipid profile of the hyperlipidemic patient. This study was thus undertaken to see the hypolipidemic effect of fenugreek seeds in patients of Type 2 Diabetes Mellitus (DM) as add-on therapy with metformin. Methods: An open-labelled comparative study of 12 weeks duration was conducted on patients (randomly divided in 2 groups of 30 each) of Type 2 DM. Group 1 was given metformin 500 mg twice a day while group 2 was given 500 mg of metformin along with fenugreek seed powder capsule, 1gm thrice a day. Evaluation for fasting lipid profile estimation was done at the beginning and at the end of the study. Student’s t-test (paired and unpaired) was applied for statistical analysis. Results: After 12 weeks of treatment, there was significant improvement in the lipid profile of both the groups. However, group 2, that received fenugreek along with metformin showed statistically greater improvement as compared to group 1 which received only metformin. Conclusions: This study shows the beneficial effects of fenugreek seeds on lipid profile in patients of Type 2 DM and can be used as an add-on therapy with metformin in controlling the lipid profile of Type 2 DM.